Determining the Effects of the Factors on FDI in Global Crisis Period - GURIS, Selahattin; SACAKLI SACILDI, Irem; GUNEREN GENC, Elif (International Journal of Economics and Financial Issues, 2014)
The purpose of this study is to analyze factors affecting Foreign Direct Investment (FDI) in countries with a high rate of FDI from 2005 to 2011, by examining the effects of the 2008 crisis. A Panel Tobit model is estimated in order to see the effects on the whole period, and classical Tobit models for each year are estimated separately for the purpose of examining the effects prior to, after and during the crisis, in detail. In the Tobit models, estimated separately for each year, the labor rate and inflation rate variables that are significant in panel Tobit models are not found significant for any of the examined years. As the balance of current accounts is found to be significant both prior to and after the crisis, it can be said that the effect of this variable on FDI is not affected by the crisis. Although there are studies examining factors affecting the FDI in the crisis period, to the best of our knowledge this is the only study using panel Tobit and classical Tobit models to that end. Keywords: Cross sectional models; panel Tobit model; foreign direct investment JEL Classifications: C21; C23; C24; F21